Study of feed granulation process based on system analysis – justification of optimization criteria - Mammadov, Mahil Isa (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
The article analyzes the process of granulation of animal feed and identifies the main criteria for optimizing this process. In order to increase the productivity of animals, the use of balanced feed is considered important. Feed granulation technology not only replaces traditional feed, but also allows the use of industrial waste (corn, sunflower residues, etc.). This process provides animals with better digestion and high feed efficiency. The results of the study show that the protein and feed unit digested when using granulated feed are maintained at a higher level than other traditional feed types. The article analyzes the stages, structural and management parameters of this technological process, and is also modeled by various system approaches (morphological, functional, information). As an optimization criterion, indicators of process energy efficiency and grain quality are taken. The efficiency of the process is measured by the amount of energy used in the granulation line, the weight and quality of the output. The article also presents functional descriptions and equipment control mechanisms to improve the granulation process. Thus, this study offers practical solutions for the systematic analysis and optimization of the granulation process of compound feeds, and emphasizes the importance of analyzing and modeling equipment based on the aggregate system.